A proteção social no SUAS: uma análise da atividade realizada pelo(as) trabalhadore(as) dos Centros de Referência de Assistência Social em João Pessoa - Cavalcante, Almira Almeida (2011)
The present study aimed to analyze the Social Protection in the Social Assistance Unified System (SUAS) from the workers of Social Assistance Reference Centres activity (CRAS) in João Pessoa city. The research proposed unveil the distance between the prescribed and the actually performed in the activity. The new settings put to the Social Assistance policy from the institution of SUAS guided by the Federal Constitution, conceived this policy as public law which strengthens the state's role in managing and breaks with the assistance character historically determined. The Social Assistance Unified System (SUAS) establishes principles and guidelines of the Social Assistance management dismembering social protection in terms of basic social protection and social protection special. This study focuses on modality of basic social protection under CRAS. To achieve the goal, firstly it was conducted a bibliographic and documentary research about the content of laws, statutes, ordinances, rules, resolutions and guidelines governing the Social Policy in Brazil and in João Pessoa city. A field research has appropriated a qualitative approach that proposes ergological studying the work from the analysis of their activity with the purpose of a better understanding of the work to transform it. Data were collected from a research collective formed by professionals, social workers and psychologists who work in CRAS. The team was divided into two working groups, seven meetings were held and it was called Labour meetings. In line with the methodology of focus group meetings it was discussed the work activity into five themes, namely: Professional Career, Real Work: Management Activity, Working Conditions, analysis of work situations and Subjective Dimension of Work. The search feature caught limits, challenges, barriers and breakthroughs that intertwine in the course of operation of social assistance under CRAS analyzed from the point of view of those who executed. Thus, the results reflect who are the workers who make up the crew of CRAS, knowledge and shared experiences, reflecting on the work situations experienced in the daily work of social assistance. This dissertative study was built in order to contribute to the management of social assistance under Cras, from the point of view of workers, aiming to understand the work and improve it.